Lung cancer biopsies: Comparison between simple 22G, 22G upgraded and 21G needle for EBUS-TBNA - Zarogoulidis, Paul; Petridis, Dimitris; Sapalidis, Konstantinos; Tsakiridis, Kosmas; Baka, Sofia; Vagionas, Anastasios; Hohenforst-Schmidt, Wolfgang; Freitag, Lutz; Huang, Haidong; Bai, Chong; Drougas, Dimitris; Theofilatou, Vasiliki; et al. (Journal of Cancer, 2020)
Introduction: Novel technologies are currently used for lung cancer diagnosis. EBUS-TBNA 22G is considered one of the most important tools. However; there are still issues with the sample size. Patients and Methods: 223 patients underwent EBUS-TBNA with a 21G Olympus needle, 22GUS Mediglobe and 22GUB Mediglobe. In order to evaluate the efficiency of 22GUB novel needle design. In order to evaluate the sample size of each needle, we constructed cell blocks and measured the different number of slices from each biopsy site. Results: The 22GUB novel needle had similar and larger number of slices from each biopsy site compared to 21G needle. Discussion: Firstly as a novel methodology we used the number of slices from the constructed cell blocks in order to evaluate the sample size. Secondly, we should seek novel needle designs and not only concentrate on the volume of the sample size.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Bronchoscopy; Cell blocks; EBUS; Lung cancer; Lymphnodes; Mediglobe; NSCLC; Olympus